The Process Teaching Portuguese Language through Genres Mathematical Texts / O Processo Ensino de Língua Portuguesa através dos Gêneros Textuais Matemáticos - Gêrlan Cardoso da Silva; osé Erlandson Kaique Lima dos Santos () (Universidade Estadual de Alagoas, 2016)
The genres are present in our days and they are making part of the whole communicative action of an person, whether through written or oral. This article aims to demonstrate the experience of a so-called workshop: Text Genre and Mathematics presented at the First Letters Seminar PROESP / UNEAL, on September 25 this year, had the purpose to integrate the Portuguese language teaching mediated genres textual through mathematics. This workshop was an interdisciplinary intervention to show how these subjects are connected, related practically at all times in the affairs and how the genres can link these two areas seen as separate and distinct. At the beginning of the workshop we present the theoretical part of what are genres and its classification. Then we show some activities with textual genres of mathematical type and how to use them in Portuguese subject and then finalize deliver some activities for participants make this interdisciplinary interaction. Some authors such as; BRAZIL (1998), Bakhtin (2000), Marcuschi (2003) among others substantiate our theoretical framework.